Genomic characterization of malignant progression in neoplastic pancreatic cysts - Michaël Noë (Nature Portfolio, 2020)
Neoplastic pancreatic cysts are associated with invasive pancreatic cancer, but their origins and evolutionary relationships are unclear. Here, the authors present the evolutionary analysis of neoplastic cysts and report them as precursors of invasive pancreatic cancer, and that SMAD4/TGFBR2 alterations are likely drivers of invasion in a subset of cases.